2012
DOI: 10.1080/09537325.2012.723687
|View full text |Cite
|
Sign up to set email alerts
|

The effect of internal and external technology sourcing on firm performance throughout the technology life cycle

Abstract: Due to copyright restrictions, the access to the full text of this article is only available via subscription.In studies about the impact of technology sourcing on firm performance, the impact of the technology life cycle has thus far received scant attention. This paper investigates this topic from the knowledge-based perspective. Data was gathered from 22 PLD (Programmable Logic Device) manufacturers in the integrated circuit industry between 1986 and 2005, and used to test two hypotheses based on panel anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Prior research confirmed a relationship among external intangibles -especially knowledge -innovation and firm performance (Jones, Lanctot, and Teegen 2001;Taylor and Lowe 1997;Tsai and Wang 2007). Nevertheless, some scholars argue that the topic is quite controversial and call for further investigation (Stolwijk et al 2012). Hence, we posit a second research hypothesis as follows: Hypothesis 2: The orientation towards externally generated intangibles is positively associated with firm performance.…”
Section: Internally Vs Externally Generated Intangiblesmentioning
confidence: 95%
See 2 more Smart Citations
“…Prior research confirmed a relationship among external intangibles -especially knowledge -innovation and firm performance (Jones, Lanctot, and Teegen 2001;Taylor and Lowe 1997;Tsai and Wang 2007). Nevertheless, some scholars argue that the topic is quite controversial and call for further investigation (Stolwijk et al 2012). Hence, we posit a second research hypothesis as follows: Hypothesis 2: The orientation towards externally generated intangibles is positively associated with firm performance.…”
Section: Internally Vs Externally Generated Intangiblesmentioning
confidence: 95%
“…The literature also emphasises the difference between internally and externally generated intangibles (Stolwijk et al 2012). The global economy and turbulent technological evolution have pushed towards the decentralisation of knowledge sourcing, and the diversification of the brand portfolio.…”
Section: Internally Vs Externally Generated Intangiblesmentioning
confidence: 99%
See 1 more Smart Citation
“…Radically, new technologies, like biopharmaceutical, are generally sourced by new entrants (Tushman and Rosenkopf, 1992). Literature has indicated that external technology sourcing in earlier technology life cycle has stronger effect (Stolwijk et al, 2012). Our findings further shows that although earlier involvement can bring more benefits it must be evaluated with consideration of entry model.…”
Section: Discussionmentioning
confidence: 66%
“…A second control variable is firm age, gauged by the years of the target firm's operation in the market. Finally, for SMEs, outsourcing is an important control variable because most SMEs lack competent in-house technical expertise and thus are more likely to outsource IT activities to external consultants (Bruneel et al 2012;Stolwijk et al 2012 Note: N = 430; Age: 1 = < 4 years; 2 = 4-6 years; 3 = 7-9 years; 4 = 10-12 years; 5 = 13-15 years; 6 = 16-18 years; 7 = 19-21 years; 8 = 22-24 years; 9 = > 25 years; Outsourcing: 0 = None; 1 = < 10%; 2 = 10-29%; 3 = 30-49%; 4 = 50-69%; 5 = > 70%.…”
Section: Control Variablesmentioning
confidence: 99%